2020
DOI: 10.1186/s12888-020-02497-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Persian version of postpartum distress measure scale

Abstract: Background: The purpose of the present study was to determine psychometric properties of the Persian version of Postpartum Distress Measure Scale (PDM Scale). Methods: In this psychometric explorative study, the data were collected using a questionnaire containing demographic information, PDM Scale, and Depression and Anxiety Stress Scale-21 (DASS-21). The content, face and construct validity of the questionnaire was examined with participation of ten experts, 10 and 150 women referring to health care centers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The same rationale was applied to the communality value identi ed for item 3 (I engaged in many different activities) of the Brazilian version of the BADS-SF, as literature points to communalities cut-off values ranging from 0.4 to 0.5 [20] and the item behaved as expected on the PCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same rationale was applied to the communality value identi ed for item 3 (I engaged in many different activities) of the Brazilian version of the BADS-SF, as literature points to communalities cut-off values ranging from 0.4 to 0.5 [20] and the item behaved as expected on the PCA.…”
Section: Discussionmentioning
confidence: 99%
“…After the process of cross-cultural adaptation, the content validity of both versions of the BADS-SF was measured using the Content Validity Index (CVI) calculation. This index measures the judges' level of agreement on how similar the adapted version is regarding comprehensiveness and representativeness when compared to the original version [19,20].…”
Section: Statistical Analysis Assessment Of the Content Validitymentioning
confidence: 99%
“…The results of this study also showed some similarities with the results of other studies performed. Shokuhi et al ( 2020 ) evaluated the Postpartum Distress Measure Scale, which showed a reliability of α = 0.94, Kassab and Hamadneh ( 2019 ) evaluated the reliability of a questionnaire to measure the midwives’ basic skills on new-born resuscitation and reported a reliability of α = 0.851. These results indicated good reliability of the tools.…”
Section: Discussionmentioning
confidence: 99%
“…The final sample size was estimated to be 32 in each group, considering 10% attrition. It is worth mentioning that the variables of postpartum distress based on the study of Shokuhi et al [ 20 ] and BSE based on the study of Shafaei et al [ 21 ] were used in determining the sample size. Finally, considering that the highest sample size was obtained with the anxiety variable, the same sample size ( n = 32 per group) was considered for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Bakht Shokuhi et al (2020) evaluated the psychometrics of PDM among the Iranian population in Tabriz and confirmed the internal consistency and stability of the results by Cronbach’s alpha of 0.72 and intra-category correlation coefficient of 0.75. The cut-off point was not reported for PDM [ 20 ].…”
Section: Methodsmentioning
confidence: 99%